Fecundando curiosidades: o sentido de se contar estórias na educação infantil - Santos, Rafael Pereira dos (2017)
The present work is a proposal of investigation on the meaning and the unfoldings that are revealed in a project of storytelling in two Centers of Early Childhood Education (CEI). For this purpose, a project was carried out for children aged 3 to 5 years in two rooms: one room in each institution and both with 25 students. The institutions are partners of the project, which belongs to a wider research called: "Panoramas of childhood and adolescence: a phenomenological study on psychoeducational actions in institutions." The research is part of the ECOFAM group (Research Group on Educational Practices and Family School and Community Psychoeducational Attention,) and has primarily the intention of approaching and creating spaces for the emergence of a dialogue between the University and the Community. The knowledge derived from such a meeting enables the University to rethink its practices, the systematization of data and its publication. For the Community, the insertion of the University allows a new reading, and especially, new actions that help in facing the issues and conflicts of everyday life. After telling six stories, two reflective interviews were made, one with each educator, in order to understand the senses that are revealed in the activity of storytelling in a CEI. The research has a qualitative character, occurs in the interventional scope and its foundations are based on the phenomenological thought